Human resources for health in India: Need to go beyond numbers - Sumant Swain; G S Preetha; Satish Kumar; Divya Aggarwal; Rajesh Kumar; Sanjiv Kumar (Wolters Kluwer Medknow Publications, 2020)
India's commitment to achieve the goal of Universal Health Coverage is evidenced by the launch of Ayushman Bharat and the transformation of Sub-Centres into Health and Wellness Centre to provide secondary and comprehensive primary healthcare to the vast majority of its population. Successful implementation of these initiatives requires adequate and skilled human resources for health and a conducive work environment. There exists a deficiency of doctors and paramedical professionals in different parts of the country. The vacancies in different categories of health functionaries have increased after 2005 despite the National Rural Health Mission/National Health Mission initiatives to strengthen the health system. The distribution of doctors and paraprofessionals in health is skewed, favoring urban areas. Properly oriented, trained, and skilled health workforce and informed public participation are critical to provide quality services for achieving national health goals. Therefore, it is necessary to establish public health cadre in all states of India and ensure appropriately skilled workforce to meet the functional requirements of health-care delivery system at different levels. This will also help to move forward on the way to reach the Sustainable Development Goals.